Effect of certain feed additives on boiler performance - Sabarinathan Nair R (Department of Poultry Science, College of Veterinary and Animal Sciences, 1976)
This thesis incorporates the findings of an investigation carried out to study the effect of terramycin, neftin furazolidone and arsenic acid on certain broiler traits of economic importance.Commercial broiler chicks were employed for the study, and were raised on litter floor. The chicks were fed broiler starter from 0-6 weeks and broiler finisher from 7-8weeks. The additives were incorporated at levels recommended by the manufactures and the duration of the study was for 8 weeks.